LEGAL STATUS OF A CHILD BORN FROM A SURROGATE MOTHER AS A RESULT OF ARTIFICIAL FERTILIZATION - GENERAL OVERVIEW - Gelukashvili, Lili; Chiglashvili, Lia (European Scientific Journal, ESJ, 2013)
The subject of a surrogate motherhood in Georgia is no longer banned in Georgia at present. There are a lot of discussions currently occurring in the society. Moreover, medical technologies have gone even further and become more efficient in this respect. Therefore, these programs have become more popular all over country. People, who formerly tried to adopt children, now think of acquiring children through this particular method, which they would be genetically bound to.